A Mountain of Debt : Navigating the Legacy of the Pandemic - Kose, M. Ayhan; Ohnsorge, Franziska; Sugawara, Naotaka (World Bank, Washington, DC, 2021)
The COVID-19 pandemic has triggered a massive increase in global debt levels and exacerbated the trade-offs between the benefits and costs of accumulating government debt. This paper examines these trade-offs by putting the recent debt boom into a historical context. It reports three major findings. First, during the 2020 global recession, both global government and private debt levels rose to record highs, and at their fastest single-year pace, in five decades. Second, the debt-financed, massive fiscal support programs implemented during the pandemic supported activity and illustrated the benefits of accumulating debt. However, as the recovery gains traction, the balance of benefits and costs of debt accumulation could increasingly tilt toward costs. Third, more than two-thirds of emerging market and developing economies are currently in government debt booms. On average, the current booms have already lasted three years longer, and are accompanied by a considerably larger fiscal deterioration, than earlier booms. About half of the earlier debt booms were associated with financial crises in emerging market and developing economies.